Porewater chemistry and magnetic parameters of a sediment core from SG1 station in the South-Eastern Mediterranean Sea - Nitai Amiel; Ron Shaar; O Sivan (PANGAEA, 2020)
A 6 m long sediment core was collected from Station SG-1 using a piston corer during a cruise on the R.V. Bat-Galim in January 2017. The sediment core was sliced onboard at intervals of 30 cm within minutes of core collection. For headspace measurements of CH~4~, approximately 1.5 mL of sediment was taken from the top of each sediment slice. This sediment was transferred immediately into N~2~-flushed crimped bottles containing 5 mL of 1.5 N NaOH. Sediment samples from the top 5 cm of each sediment slice were transferred to vials under anaerobic conditions, and porewater was extracted from them on the same day by centrifugation at 4°C under an N~2~ atmosphere. The supernatant was filtered through a 0.22 μm filter and was analyzed for dissolved Fe^2+^, sulfide, and sulfate. The sediment was dried in an ambient temperate under N~2~ atmosphere, the dry sediment was analyzed for different iron minerals fractions following the sequential extraction protocol from Poulton and Canfield (2005, doi:10.1016/j.chemgeo.2004.09.003). The 30 cm core segments were split along their length and sampled for magnetic analysis by pushing non-magnetic plastic sampling boxes of 23x23x19 mm into the split halves at ~5 cm intervals. The different microbial respiration pathways cause changes in the porewater chemistry and in the sediment mineralogy due to the reduction and dissolution of iron minerals. In this study, we linked the different respiration processes to the magnetic parameters of a 6 m sediment core from the South-Eastern Mediterranean Sea. In the sulfate-methane transition zone (SMTZ), we observed a decrease in the sediment magnetic properties, due to the dissolution of detrital magnetic minerals, followed by pyrite precipitation. In the upper methanic zone, where iron-reduction occurs, we observed an increase in magnetic properties due to precipitation of authigenic ferrimagnetic minerals.